Sejarah Masuk dan Perkembangan Ahmadiyah di Sulawesi Selatan - Barsihannor Barsihannor (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2009)
Ahmadiyah is one of theological schools in Islam. Its theological thinking controversy impacts on religious attitude of the society in common. Thus, they declare Ahmadiyah is deviant teaching and reject Ahmadiyah's concepts claiming that Ghulam Ahmad is a prophet, revelation acceptor, and Messiah as well as al-Masih al-Mau'ud. For this reason, Ahmadiyah has been undergoing many obstacles to spread its mission. in spite of rejecting its thelogical concept and mission movement, people in South Sulawesi do not reject the existence of Ahmadiyah's people and they also refuse to have physical violence to them. They, indeed, consider that Ahmadiyah's people should be protected and given their right to life. These amicable and tolerant attitudes are due to its core value of the cultures. Therefore Ahmadiyah could live well together with other communities in South Sulawesi.